Curriculum Management in Islamic Boarding Schools: Integrating the Study of Kitab Kuning and Quranic Memorization (Tahfidz) - Hafiedh Hasan; Ariani; Anisah Ummi Kulsum (EDUJAVARE: International Journal of Educational Research, 2026)
Curriculum management in Islamic boarding schools is seen as a necessity for survival amidst competition and globalization, as well as a foundation for future development. Curriculum management plays a crucial role in supporting the success of memorization programs in Islamic educational institutions. This paper aims to explore the concept of implementing curriculum management in the learning of the yellow books and Quran memorization in Islamic boarding schools. Through proper and correct management of the learning of the yellow books and Quran memorization, it is hoped that optimal learning outcomes can be achieved. The study employed a library research method, using sources in the form of journals and books retrieved from Google School. The results indicate that the management of the yellow books curriculum in Islamic boarding schools is implemented in an integrated manner, as the integrated curriculum utilizes a learning approach that enables students, both individually and in groups, to actively explore, explore, and discover concepts. Furthermore, this integrated curriculum is a new curriculum without abandoning the previous curriculum model. Therefore, the integration of the old and new curriculum models can strengthen Islamic boarding schools as unique, creative, and distinctive institutions.